Smart choices? An experimental study of smart meters and time-of-use tariffs in Ireland - Cameron A. Belton; Pete Lunn (The Economic and Social Research Institute (ESRI), 2019)
The introduction of smart technology and dynamic tariffs (such as time-of-use tariffs) provides multiple potential benefits for electricity markets. However, time-of-use tariffs represent an additional complexity for consumer tariff choices in electricity markets. How well consumers may choose between different types of tariffs, and whether certain tools can improve these choices, are therefore important questions for energy regulators and policy makers. This paper presents the results of an exploratory study that used experimental behavioural science to explore the issue of consumer choice in electricity markets for time-of-use tariffs. A representative sample of consumers (n= 145) were given information about smart meters and time-of-use tariffs. Attitudes towards smart meters and comprehension and choice quality between different types of electricity tariffs (judged against participants' own perceptions of their electricity usage) was measured through a sequence of experimental tasks. Findings suggest that a general aversion to time-of-use tariffs may lead to sub-optimal choices between different types of tariffs. Participants were also asked to choose between different priced time-of-use tariffs via an experimental price comparison site. Tools which facilitate personalised estimated costs were shown to significantly improve decision-making between such tariffs. Potential policy implications, in light of these findings, are discussed.
Keywords: 330; smart meter; time-of-use tariff; consumer choice; behavioural economics